INTERPRETING FARMER ATTITUDE TO FOOD LOSS PHENOMENON IN THE FRESH MILK SUPPLY CHAIN IN BANYUMAS, INDONESIA - Iftita, Denok Meinar; Romadlon, Fauzan; Karima, Halim Qista (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Food loss is currently a global problem for both developing and developed countries. Food loss is defined as the loss of a portion of food that is still raw but cannot be processed into a food product because the resulting material does not meet the desired quality. Food loss occurs in livestock production, and one focus is the milk supply chain. Food loss in milking usually occurs due to activities carried out during the harvest, post-harvest, and distribution processes. Food loss in the milk supply chain is caused by decreased milk quality and the farmer's attitude. Problems regarding the attitude of farmers that often occur are farmers' low attitude of responsibility to conduct something. This study aims to determine the effect of farmer attitudes to food loss in the milk supply chain. The method used was quantitative by collecting data from a survey of 46 milk farmers in Bayumas. Then, data were analyzed using the ANOVA approach. The results showed that demographics significantly affect farmers’ attitudes toward food loss in the milk supply chain. The food loss is due to farmers' treatments, including feeding, filtering milk into milk cans, and depositing milk in the shelter. Most farmers are over 50 and need more attention and knowledge about food loss in the milk supply chain. Therefore, it is necessary to conduct regular counseling programs for farmers in the supply chain regarding food loss mitigation. The stakeholders can provide the program to add new insights related to food loss. There should be intervention from the deposit shelter and cooperative in helping to increase farmers' awareness of food loss in quantity and quality.